Smart School Safety: Deteksi Dini Bencana Berbasis Arduino di SMK Pulau Berayan Medan - Leman, Dedi; Rahman, Maulia; Harahap, Nurmahendra (Unity Academy, 2025)
School security is a crucial aspect in creating a safe and conducive learning environment. One significant threat to school security is natural disasters, which can occur suddenly and jeopardise the safety of students and staff. This service activity aims to develop and implement an Arduino-based disaster early detection system at SMK Swasta Pulau Berayan Darat Medan. The system is designed to provide real-time warnings of potential disasters such as earthquakes, fires, and floods through the integration of various sensors linked to alarms and notifications. The main contribution of this activity is the availability of disaster detection devices that are cheap, adaptive, and easy to operate by the school. The implementation of the system succeeded in increasing the alertness of the school community, as shown by an 85% increase in understanding of evacuation procedures based on the results of questionnaires before and after the training. In addition, 95% of respondents stated that the system provides a sense of security. These results show that the Arduino-based disaster early detection system has the potential to become a security model that can be implemented in other schools to support the creation of a safer and more disaster-responsive educational environment.